Basic Characteristics And Curriculum Planning Stages At MTS Assalaam Bandung - Fitriyani Kosasih; Asep Dani Alamsyah; Pipit Sugiarto; Erwin Erwin (Universitas Muhammadiyah Enrekang, 2022)
The research objective was to obtain an overview and analyze the characteristics of the stages and curriculum planning at MTS Assalaam Bandung. This study uses a qualitative approach. The results of the study show that the learning program at MTS Assalaam Bandung school is structured based on National Standards to form a generation of Qur'ani who are smart, pious, skilled and have noble character. MTS As-Salaam Bandung has a tahfidz quran program with an orientation of 30 chapters in less than two years. The MTS Assalaam Bandung curriculum is a curriculum that is integrated with the school curriculum and the Ministry of Religion curriculum. In the Assalaam MTS curriculum there is a requirement that requires students to study and also live in dormitories with the aim of being able to support the achievements and abilities of students who receive 24-hour guidance at Islamic boarding schools. The study of religious knowledge taught at MTS Assalaam Bandung with reference to the yellow book, namely the book Akhlakul banin, banat, tijan, ta'lim, tashrif and taqrib. All of these books are integrated with general lessons so that students do not only have general knowledge skills but have integrative knowledge that leads to vertical piety as well as horizontal piety.